ISLAM DAN DEMOKRASI DARI ERA TAHTAWI HINGGA GHANNOUCHI - Maftuh Maftuh (MIYAH : Jurnal Studi Islam, 2020)
Abstract: This research was conducted to examine the history of debate among Muslim intellectuals about Islam and democracy from the Tahtawi to Gannouchi eras, and its relevance to contemporary Islamic movements in parts of the Arab world. A long discussion of Azzam Tamimi's writings on the relationship between Islam and democracy, with a historical approach, leads to a conclusion. In the Islamic tradition, there are at least two major variants, namely fundamentalist and modernist groups. Fundamentalist groups are generally more rigid when adapting democracy to Islam, even shifting towards radicalism; while modernists are more adaptative in accepting democratic discourse. The results of this study can take an understanding that the concepts discussed by the characters. From the Tahtawi era to Gannouchi, it has had a distinct significance in the contribution of discourse between Islam and democracy. These concepts have clearly contributed to or input in the link between Islam and democracy. Although, some figures appear to be taking careful steps in explaining their ideas, so as not to be followed by Western democratic thinking which is rather free.Keyword: Islamic Democratic, Contemporary Islamic movement